Synthesis and behavior of novel sulfonated water-soluble N-heterocyclic carbene (η4-diene) platinum(0) complexes - Ruiz Varilla, Andrea M. (2015)
A series of water-soluble (NHC)Pt(0)(dvtms) and (NHC)Pt(0)(AE) complexes containing different sulfonated NHC ligands (dvtms = divinyltetramethyldisiloxane and AE = diallyl ether) are reported. The dvtms compounds have been found to be quite robust and to display some conformational rigidity, whereas their AE counterparts are less stable and more flexible. The catalytic evaluation of these complexes in the hydrosilylation of alkynes in water revealed no benefits in favor of the complexes containing the more labile spectator diene (AE), and a fairly regular catalytic behavior for all complexes that restricts the location of the sulfonate group to the proximity of the metal site.